ISLAMIZATION CONSUMPTION BEHAVIOR CONCEPT (ISLAMIC OFFER IN CONSUMPTION BEHAVIOR IN THE ALFA GENERATION) - Hakim, Muhamad Arief Al; Umam, Khoirul; Yaqqin, Aynul; Trigiyatno, Ali; Muhtarom, Ali (istinbath, 2024)
The current needs system is no longer determined by real needs but has been regulated with the existence of commodity goods. Society's system of consumption changes rapidly to follow the system of needs so that the consumption of goods and services is no longer a necessity but a desire of every individual who is swept up in the consumptive world. Consumerism culture is considered a culture that must be attached to society in order to obtain an identity. Even though the Prophet Muhammad and his companions, preferred to give infaq fi sabilillah, even well waqf by Utsman Bin Affan, rather than simply consuming a commodity that was not useful and did not spend their wealth on something without benefit, especially for an impossible lifestyle, including using their wealth in moderation. This study uses the literary method to search for various literature sourced from journals and books that have to do with consumerism, consumption, and consumption behavior. The results of the study explain that consumerism which is based on the principles of utilitarianism and rationality alone, encourages consumers to maximize use value without regard to human values and even Islamic values, as a result, creates individualism and self-interest. There are at least 5 points that need to be implemented in Islamic offers in consumption behavior, including 1) Paying attention to priority scales in consuming a commodity, 2) Following Islamic norms in consumption behavior, 3) Maintaining Maqoshid Syariah with the aim of benefiting individuals and society, 4) Comply with the principles of halal and haram, 5) Consumption behavior is part of increasing worship.